Reinterpretasi Ketentuan Hukum terhadap Anak Akibat dari Perkawinan Siri di Indonesia - Harahap, Irwan Safaruddin (Pagaruyuang Law Journal, 2018)
This paper attempts to examine the protection of siri married children by focusing on the problem (1) How is the Protection of the Law against the Child from the unregistered marriages? and (2) How is the position of a child born of unregistered marriages to inheritance? The results revealed that (1) Protection of the Law against the Child from the Betel Betrayal The position of the child in Islamic law still obtains the same recognition as the registered marriage. However, in the eyes of state law, in the absence of a marriage certificate of his parents, the child's birth certificate does not contain the name of his biological father and only the name of the mother who gave birth. (2) Position of a child born of unregistered marriages to inheritance. The child is considered as a child outside marriage so that it can not do legal relationship with civil father biologisnya, but with the decision of the Constitutional Court the child has a civil relationship with a biological father and his father's family. Currently in our positive legal system there is a change, both the status of the inheritance rights of the siri daughter, where now the child of the siri marriage can sue for civil rights from his father. Currently the government will issue a birth certificate that records the father's name of the child of the marriage series. The law commands the recognition of a child born of a marriage that is lawful according to religious law, but is not yet lawful by country.